2006
DOI: 10.1096/fj.05-5231fje
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of riproximin, a new type II ribosome‐inactivating protein with antineoplastic activity from Ximenia americana

Abstract: The aim of this study was to identify and characterize the active component(s) of Ximenia americana plant material used to treat cancer in African traditional medicine. By a combination of preextraction, extraction, ion exchange and affinity chromatography, a mixture of two cytotoxic proteins was isolated. Using degenerated primers designed on the de novo sequence of two tryptic peptides from one of these proteins, a DNA fragment was amplified and the sequence obtained was used to determine the complete cDNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 35 publications
0
40
0
Order By: Relevance
“…An increase in riproximin cytotoxicity was observed upon neuraminidase treatment for the strongly sialylated MDA-MB-231 cells but not for the sialyl-poor MCF7 (46), the most sensitive cell line within the panel tested (2). This experiment demonstrated a direct relationship between the biological activity of riproximin and the extent of sialylation found on cell surfaces.…”
Section: Na2/na3 and Cancer-related Clustered Tn Glycostructuresmentioning
confidence: 75%
See 2 more Smart Citations
“…An increase in riproximin cytotoxicity was observed upon neuraminidase treatment for the strongly sialylated MDA-MB-231 cells but not for the sialyl-poor MCF7 (46), the most sensitive cell line within the panel tested (2). This experiment demonstrated a direct relationship between the biological activity of riproximin and the extent of sialylation found on cell surfaces.…”
Section: Na2/na3 and Cancer-related Clustered Tn Glycostructuresmentioning
confidence: 75%
“…Riproximin specificity for the clustered Tn antigen is remarkable and could explain its tumor specificity described previously (1,2). Prominent targets for riproximin on cancer cells could therefore be the cancer-associated mucins (MUCs).…”
Section: Na2/na3 and Cancer-related Clustered Tn Glycostructuresmentioning
confidence: 80%
See 1 more Smart Citation
“…1 These proteins consist of two chains, which exhibit complementary properties. 2 The A chain is an rRNA N-glycosidase, which causes depurination of the 28S rRNA in a catalytic manner and thus leads to transcriptional arrest by inhibiting protein synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…We reasoned that it would be worth investigating 2 , and Martin R Berger the activity of Rpx in PDAC models, because a colorectal cancer liver metastasis model had shown explicit antineoplastic activity. 1 Moreover, the affinity of Rpx for carcinoembryonic antigen (CEA) 5 suggested that neoplasias expressing this glycoprotein might be preferential targets. Therefore, we determined the sensitivity of 17 PDAC cell lines to Rpx and investigated in a newly established PDAC liver metastasis model, whether Rpx has antineoplastic efficacy against PDAC cells growing in rat liver.…”
Section: Introductionmentioning
confidence: 99%